The Determinants of the Value Created by Stock Repurchase Programs - Hamouda, Foued; Ben Arab, Mounira (Revue Gouvernance / Governance Review)

(untitled) (Centre d’études en gouvernance de l’Université d’Ottawa, 2009)
This paper aims to extend the empirical literature on the determinants of the value created by stock repurchase programs by analyzing the characteristics of the repurchase decision-making groups. Based on a sample of 200 US-listed firms from 1998-2004, the paper examines empirically the relationship between value created by stock repurchase programs and board of directors’ characteristics. The analysis depends on panel data analysis to consider unobservable fixed-effects in this relationship.The results provide evidence of a significant relation between board of directors’ characteristics and value created by the stock repurchase programs. The two important determinants are directors’ independence and directors’ outside experience. However, we find that this relationship changed significantly for some measures after the adoption of the 2002 Sarbanes-Oxley Act.